The strange case of Laetesia raveni n. sp., a green linyphiid spider from Eastern Australia with a preference for thorny plants (Araneae, Linyphiidae) - Hormiga, Gustavo; Scharff, Nikolaj (Zootaxa, 2014)
Laetesia raveni n. sp. (Araneae, Linyphiidae), is described based on specimens collected in New South Wales and Queensland (Australia). This new linyphiid species is of bright green colour, and it seems to have a preference to build its webs almost exclusively on two plant species, namely Calamus muelleri Wendland (Arecaceae) and Solanum inaequilaterum Domin, (Solanaceae), both of them densely covered with thorns. The epigynal morphology of Laetesia raveni n. sp. varies intraspecifically. Live individuals and several of their dome-shaped sheet webs are illustrated.